What is a Water Footprint?: An Overview and Applications in Agriculture - Daniel R. Dourte; Clyde W. Fraisse (EDIS, 2012)
Agriculture is by far the largest global consumer of freshwater. Comparing water footprints of different management practices in agriculture can help evaluate drought tolerance, water use efficiency, the effective use of rainfall, and the significance of irrigation. Scientists are thinking about ways to adapt agricultural systems to a changing climate, especially precipitation changes, so the water footprint is a useful measure to compare resilience of agricultural systems to droughts and dry spells. This 11-page fact sheet was written by Daniel R. Dourte and Clyde W. Fraisse, and published by the UF Department of Agricultural and Biological Engineering, January 2012.